Better economic regulation: The role of the regulator - OECD; International Transport Forum (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2011)
Good transport services contribute strongly to the productivity of an economy and extend the range of activities accessible to consumers. Good services require adequate infrastructure and reasonable usage conditions to that infrastructure. Much transport infrastructure is capital intensive and lumpy. Such cost structures imply that there will be few service providers. In some circumstances the structure of costs and technology is such that economic regulation is the best way to drive efficient outcomes. Achieving the right governance structures - including the question of when to regulate and how to regulate - is central to performance of the sector and the subject of this paper, which summarises discussions at a Roundtable held in December 2010.
Keywords: 330